Regional Government Strategy for Improving Services to the Community Through Electronic-Based Government Systems - Damay Rusli (Jurnal Sosial Sains dan Komunikasi, 2023)
The implementation of an Electronic-Based Government System (SPBE) in Regional Government is aimed at realizing efficient, effective, transparent and accountable work processes, as well as improving the quality of public services. In order for the implementation of SPBE to run according to its objectives, its implementation needs to be regulated based on the principles of Good Governance. This research uses descriptive analysis as a research method, using a qualitative approach and the research results explain that the implementation of good governance can realize people's aspirations in achieving the goals and aspirations of the nation and state. So it is necessary to develop and implement a clear and real system of participation, transparency and accountability so that the implementation of SPBE in Regional Government can take place in an efficient, successful, clean and responsible manner. Apart from that, innovation in implementing SPBE also provides opportunities to realize policy directions and strategies in order to produce faster, better and cheaper supervision systems, government administration systems and public services. On the other hand, regional governments also need to transform government paradigms and processes by integrating planning services, budgeting services, procurement services and electronic-based performance management services. This will create an HR culture for ASN employees who are able to think creatively, systemically, have a global perspective, have a high work ethic, are able to manage strategic environmental changes, and provide proactive services in accordance with community needs.